Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752